LIFE OF YOGA AND NEO-HINDUISM: IDENTITIES AND BELONGINGS VIDA DE YOGA E NEO-HIDUÍSMO: IDENTIDADES E PER-TENCIMENTOS - Ladeira, Thaís Assis; Bastos, Cecilia (Sociologia & Antropologia, 2024)
This article addresses the themes of embodiment of tradition and the building of new religious identities by the case study of a Vedanta group in Rio de Janeiro. From the historical context of the transnational movements that have propagated practices and beliefs of Hindu origin, we present the interlocutors’ religious identifications and lifestyles. We then discuss the tensions and contradictions involved in the discourses, to some extent ambiguous, about autonomy and belonging. The data collected in the field reveals the meanings of a life of yoga and the different levels of engagement with the Hindu tradition and its practices and rituals. Beyond the notion of conversion, we argue that the construction of this neo-Hindu identity not only involves restrictions and adaptations to traditional precepts, but also a creative experience of transformation through the choice of certain prescriptions, identifications, and behaviours.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Identidade; Identity; Neo-Hinduism; Neo-hinduísmo; Pertencimento religioso; Religious belonging; Tradition; Tradição; Vedanta; Vedanta